1998
DOI: 10.1083/jcb.142.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regulated Expression of Mutant RhoA and Rac1 Small GTPases on the Development of Epithelial (MDCK) Cell Polarity

Abstract: MDCK cells expressing RhoA or Rac1 mutants under control of the tetracycline repressible transactivator were used to examine short-term effects of known amounts of each mutant before, during, or after development of cell polarity. At low cell density, Rac1V12 cells had a flattened morphology and intact cell–cell contacts, whereas Rac1N17 cells were tightly compacted. Abnormal intracellular aggregates formed between Rac1N17, F-actin, and E-cadherin in these nonpolarized cells. At all subsequent stages of polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
262
2
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(291 citation statements)
references
References 47 publications
24
262
2
3
Order By: Relevance
“…2A and B). Consistent with earlier observations (Hordijk et al 1997;Takaishi et al 1997;Jou & Nelson 1998;Kodama et al 1999), both proteins increased the accumulation of F-actin (data not shown) and E-cadherin at cell-cell AJs in MDCK cells ( Fig. 2C and D).…”
Section: Inability Of Cdc42 and Rac To Induce The Formation Of Microssupporting
confidence: 92%
See 1 more Smart Citation
“…2A and B). Consistent with earlier observations (Hordijk et al 1997;Takaishi et al 1997;Jou & Nelson 1998;Kodama et al 1999), both proteins increased the accumulation of F-actin (data not shown) and E-cadherin at cell-cell AJs in MDCK cells ( Fig. 2C and D).…”
Section: Inability Of Cdc42 and Rac To Induce The Formation Of Microssupporting
confidence: 92%
“…A recent series of experiments on the roles of the Rho small G protein family, including the Rho, Rac and Cdc42 subfamilies, in cultured MDCK cells have revealed that the Rho subfamily (Rho) regulates the formation of stress ®bres and focal adhesions, whereas the Cdc42 and Rac subfamilies (Cdc42 and Rac) regulate the accumulation of actin ®laments (F-actin) and E-cadherin at cadherin-based cell-cell adherens junctions (AJs) (Hordijk et al 1997;Takaishi et al 1997;Jou & Nelson 1998;Kodama et al 1999). Rho does not directly affect the accumulation of F-actin or E-cadherin at cell-cell AJs, although it indirectly affects it .…”
Section: Introductionmentioning
confidence: 99%
“…p120 ctn also alters the relative activities of the small G-proteins Rho A, Rac, and Cdc42 Grosheva et al, 2000;Noren et al, 2000). This may well be related to changes in the activities of these proteins initiated by adhesion Noren et al, 2001) and involved in actin-driven cadherin clustering (Braga et al, 1997(Braga et al, , 1999Jou and Nelson, 1998;Takaishi et al, 1997).…”
Section: The Plot Regulatory Interactions At the Cytoplasmic Domain Omentioning
confidence: 99%
“…In addition, scribble has 16 canonical leucine-rich repeats (LRRs), another protein -protein interaction motif. Related repeats to the LRRs are known to bind small GTPases of the Ras superfamily (Jou and Nelson, 1998;Kaibuchi et al, 1999). Recently, proteins with both PDZ domains and LRRs have been reported to have common functions in the control of the cell shape and polarity.…”
mentioning
confidence: 99%